Impact of the chain length on the biodistribution profiles of PEGylated iron oxide nanoparticles: a multimodal imaging study. Issue 25 (16th June 2021) - Stanicki, Dimitri; Larbanoix, Lionel; Boutry, Sébastien; Vangijzegem, Thomas; Ternad, Indiana; Garifo, Sarah; Muller, Robert N.; Laurent, Sophie
Abstract : Bimodal sub-5 nm superparamagnetic iron oxide nanoparticles (SPIO-5) coated with polyethylene glycol of different chain lengths ( i.e. PEG-800, -2000 and -5000) have been prepared and characterized. Abstract : Bimodal sub-5 nm superparamagnetic iron oxide nanoparticles (SPIO-5) coated with polyethylene glycol of different chain lengths ( i.e. PEG-800, -2000 and -5000) have been prepared and characterized. Fluorescence properties have been obtained by mean of the grafting of a near-infrared-emitting dye (NIR-dye) onto the surface of the oxide, thanks to the carboxylic acid functions introduced towards an organosilane coating. Such modification allowed us to follow in vivo their biodistribution and elimination pathways by T 1 –w and T 2 –w high-field magnetic resonance imaging (MRI), as well as by optical and optoacoustic imaging. Interestingly, it has been highlighted that for a given composition, the thickness of the coating strongly influences the pharmacokinetic properties of the administrated SPIO-5.